A facile naphthalene-based fluorescent chemodosimeter for mercury ions in aqueous solution1. Issue 22 (11th March 2015) - Han, Yifeng; Yang, Chengyu; Wu, Kai; Chen, Yu; Zhou, Baocheng; Xia, Min
<x xml:space="preserve">Abstract</x> A facile naphthalene-based fluorescence "turn-on" chemodosimeter for rapid, selective and sensitive detection of Hg2+ by mercury-promoted hydrolysis of the vinylether group has been reported.